WORKING VALUES AND WORK-LIFE BALANCE FROM THE PERSPECTIVE OF GENERATIONS X, Y, Z (Third Sector Social Economic Review, 2023)
Generational differences can be shaped by a variety of factors such as technology, social, economic and cultural changes. From the perspective of the X, Y, Z generations, the way in which the relationship between work values and work-life balance develops comes to the fore. For this reason, the relationship between the work-life balance and work values of generational differences was examined and in this direction, the differences and similarities between the work-life balance and work values of the X generation who are the managers of business life, the Y generation who are the young managers and professionals, and the Z generation who have just started their business life. examined. In this respect, it is the first study in the literature. The study was designed as a cross-sectional survey model, one of the quantitative research designs. With the convenience sampling strategy, 343 samples participated in the study. According to the findings obtained, although no statistically significant difference was found in terms of generational differences and income level variable, when looked from the perspective of working values, it was seen that gender affected the working values. After the application of the work-life balance scale, it was determined that only the income level made a significant difference between the variables.
Keywords: Study Values; Work-Life Balance; Generation Z; Generation Y; Generation X